Effects of irrigation on the ecological services in an intensive agricultural region in China: A trade-off perspective. (10th July 2017) - Li, Ruihua; Lin, Hua; Niu, Haipeng; Chen, Yuqi; Zhao, Suxia; Fan, Liangxin
Abstract: The quantification of the effect of irrigation on crop yields and other non-marketed ecological services (ESs) is crucial to maintain a steady increase in agricultural production while minimizing negative environmental effects. We use the modified ES trade-off concept frame to analyze the interrelationships between crop yield income and nitrogen leaching, nitrous oxide emission, and soil organic carbon (SOC) sequestration by simulating crop output and other non-marketed ESs with a process-based denitrification–decomposition model. Results show that positive trade-offs and synergies exist between crop yield income and nitrogen leaching, nitrous oxide emission, and SOC sequestration at the loam site before the irrigation index reaches 0.7. Similarly, a positive trade-off exists between crop yield income and nitrogen leaching at the sandy soil site, and a positive synergy occurs between crop yield income and SOC sequestration at the loam site as the irrigation index increases from 0 to 1. The extended ES trade-off concept frame is a beneficial approach for optimizing current agricultural irrigation management strategies to maintain sustainable agricultural development. Highlights: Classifying the trade-offs and synergies between ecological services. Income Consumption Curve was used to quantify the "win–win" relationship between ecological services. Increasing irrigation exerts positive effects on the ecological services before irrigation index reaches 0.7. The inflection interval of the ecological services changing is between irrigation indexes of 0.7 and 0.8.